2008
DOI: 10.1016/j.exger.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

T-cells from advanced atherosclerotic lesions recognize hHSP60 and have a restricted T-cell receptor repertoire

Abstract: Atherosclerosis is a multifactorial, chronic-inflammatory disease for which the underlying cause remains unknown. It is also well documented that T-cells are among the first cells to migrate into the arterial intimal vessel layer, but their function there is still unexplained. Clinical and experimental data have provided evidence that atherosclerosis starts as an autoimmune reaction based on humoral and cellular immunity against a phylogenetically highly conserved stress protein, heat shock protein 60 (HSP60).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 24 publications
3
39
0
2
Order By: Relevance
“…The question of clonality of resident T cells in atherosclerotic lesions has also been addressed, with contrasting results. Initial data pointed to a polyclonal origin for T cells in plaques (45,46), but more recent studies demonstrated that resident T cells were locally activated by OxLDL and heat shock protein, using a restricted TCR repertoire (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…The question of clonality of resident T cells in atherosclerotic lesions has also been addressed, with contrasting results. Initial data pointed to a polyclonal origin for T cells in plaques (45,46), but more recent studies demonstrated that resident T cells were locally activated by OxLDL and heat shock protein, using a restricted TCR repertoire (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Genetically normocholesterolemic rabbits immunized with mbHSP65 (in the present context, mbHSP65 is always used as a paradigmatic and potent representative of bacterial HSP60) develop atherosclerotic plaques irrespective of their diet with low or high-cholesterol levels, and T cells isolated from these lesions specifically respond to mbHSP65 in vitro (Xu et al , 1993aMetzler et al 1999), a finding similar to that in humans (Rossmann et al 2008;Benagiano et al 2005). Both C57BL/6J mice, fed high-cholesterol diet, and LDLr −/− mice, fed a normal chow diet, revealed enhanced early atherosclerotic lesions after immunization with mbHSP65 (Afek et al 2000;George et al 1999).…”
Section: Hsp60 In Experimental Atherosclerosismentioning
confidence: 57%
“…These DCs can function as antigen-presenting cells (APCs) and thereby capture potentially harmful exogenous or autoantigens and present these to T cells and macrophages. Lesion-derived T cells display an oligoclonally restricted repertoire in contrast to the polyclonal pattern of peripheral blood mononuclear cells (PBMCs), indicating that oligoclonal T cell expansion can take place in human atherosclerotic lesions (Rossmann et al 2008). We have recently shown that these early autoreactive intralesional T cells, derived from early, clinically still inapparent human atherosclerotic lesions, can specifically react to certain hHPS60 epitopes (Almanzar et al 2012).…”
Section: Hsp60 In Human Atherosclerosismentioning
confidence: 99%
“…As a matter of fact, this goal has already been achieved for arthritogenic and arthritoprotective HSP60 T-cell epitopes (Prakken et al 1997;van Eden and Waksman 2003), while for atherosclerosis, this is only true for B-cell epitopes (Perschinka et al 2003(Perschinka et al , 2007. However, similar to the situation in synovial tissues of animals and humans, accumulation of HSP60-reactive T cells in atherosclerotic plaques compared to peripheral blood was found in humans (Benagiano et al 2003(Benagiano et al , 2005 and rabbits (Rossmann et al 2008;Xu et al 1993a). In mice, the disease could be transferred by HSP60-specific T cells to syngeneic recipients (George et al 2001).…”
Section: Discussionmentioning
confidence: 89%